Educação musical e currículo: diversidade cultural na formação docente em Música - SANTOS, Micael Carvalho dos (2020)
This paper presents a discussion on the epistemological bases of teacher education in music from the analysis of the curriculum. As the object of this research, we highlight the relations about cultural diversity in the formative processes of music teachers in the state of Maranhão. In this way, we present dialogues between music education and ethnomusicology in the possible contributions in the scope of musical diversity in this formative path. The curriculum, as a space of dispute and power, can be a place of diverse knowledges that build emancipation of the human being; can also envolve the multiple artistic manifestations and expressiveness that occur in musicality - inherent to human beings - from different cultures in the world. Undergraduate courses in Music at UEMA and UFMA, in the city of São Luís, were chosen as the places of the research that aims to understand the Music curriculum, from the conception of cultural diversity, in undergraduate courses in Music at UEMA and UFMA. As the specific objectives we defined the identification of the configuration of the music licensing curricula of UEMA and UFMA from the Political Pedagogical Project; the investigation of the concepts of cultural diversity present in the faculty and students of the courses; the relations between the specificities of the Music curriculum studied and political and social issues and identification of the possible relations between Music Education and Ethnomusicology in the selection of cultural diversity for the teacher education in Music. This investigation is characterized as a Case. As a data collection instrument, we used the semi-structured interview with teachers of the Structuring Teaching Nucleus and undergraduate students of the last period in the selected courses. We discussed the curriculum and the qualification of teachers in understanding educational work in the context of music education. We also bring the discussion to the context of the state of Maranhão with a historical survey on the Music degree courses existing in the capital. We analyzed the results and discussed the formative paths of teaching music in the perspective of the subjects participating in the investigation. As considerations, we believe that different musical knowledge should be included in the music curricula in order to provide significant conditions for working with cultural diversity. We also think that the legitimation of the different knowledge in these paths reveals the openness to break with the Eurocentric vision that is still present in these formations. We note that some themes are still considered minority approaches or totally absent in the curricula of the researched courses, such as the identification of local manifestations that the researched curricula need to contemplate and make closer relations with popular culture and the reality of basic education. Regarding the theoretical perspective of curriculum, we identified that both courses have mixed foundations, with aspects of traditional theory, critical theory and with less influence on post-critical theory. Keywords: